Burundi's seed systems improve livelihoods - Rubyogo, Jean-Claude (International Center for Tropical Agriculture, 2011)
Long-term civil unrest has forced the long-suffering citizens of Burundi to identify closely with food aid. However, when emergency aid was lacking, constant hardship obliged people to acquire survival strategies, such as growing resilient subsistence crops like the common bean. Their ability to continue planting this often neglected crop during the darkest periods became their lifeline. The Pan-Africa Bean Research Alliance (PABRA) saw the demand for beans in Burundi, and recognized the crop's adaptability and potential. It kick-started its bean improvement efforts in the late 1990s by developing suitable varieties and improving local ones, generating markets for farmers; extra produce to earn income and, more recently, introducing climbing beans in the country. To boost the bean production process and facilitated by the International Center for Tropical Agriculture (CIAT, its Spanish acronym), PABRA linked up with Burundi's national program: the Institut des Sciences Agronomiques du Burundi (ISABU).